Adolescent-friendly health services in primary healthcare facilities in Malaysia and its correlation with adolescent satisfaction level. Issue 1 (31st December 2020) - Awang, Hafizuddin; Ab Rahman, Azriani; Sukeri, Surianti; Hashim, Noran; Nik Abdul Rashid, Nik Rubiah
ABSTRACT: A cross-sectional study through clinic assessment and adolescent satisfaction survey was conducted in a Malaysian state to determine the proportion of clinics that provided adolescent-friendly health services, identify the crucial criteria for the provision of adolescent-friendly health services and determine the correlation of adolescent-friendliness level with the satisfaction level of adolescents. Out of 85 clinics, only 35.3% (95%CI: 0.25, 0.46) can be regarded as adolescent-friendly clinics. Large clinics showed significantly [F(2, 84) = 13.82, p < 0.001] higher mean score than smaller clinics. Adolescent-friendly clinics had significantly (p < 0.05) higher mean score in 11 of 12 criteria of best practices than conventional clinics. Adolescents were more satisfied with the health services provided by adolescent-friendly clinics than conventional clinics (p < 0.05). There is a significantly (p < 0.05) strong correlation between clinic assessment score and adolescent satisfaction level (r = 0.643). This study provides important insight for the Ministry of Health to strengthen the provision of adolescent-friendly health services in Malaysia.